2021
DOI: 10.47067/reads.v7i2.349
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Exchange Rate and Oil Prices on Inflation in Pakistan

Abstract: This study investigates the impact of Exchange Rate (Rupees Vs US $) and oil prices (Pak. Petroleum) and on the inflation rate in Pakistan by applying the Co-Integration technique to the monthly data for all the three series ranging from January 2004 to January 2019.  Unit root testing results provide strong statistical evidence for each of the series to be non-stationary at the level and stationary at first difference. Co-integration testing results confirm the existence of Cointegration among the selected ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…So, it can be concluded that lower pump diesel and petrol prices significantly decline inflation in Pakistan. The results of this study are consistent with those of (Qasim et al, 2021;Iqbal et al, 2021;Malik, 2016;Saleem & Ahmad, 2015).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…So, it can be concluded that lower pump diesel and petrol prices significantly decline inflation in Pakistan. The results of this study are consistent with those of (Qasim et al, 2021;Iqbal et al, 2021;Malik, 2016;Saleem & Ahmad, 2015).…”
Section: Resultssupporting
confidence: 91%
“…This study is different from previous studies on the research topic as it measures energy prices in domestic pump diesel prices and pump gasoline prices. While the previous studies have measured the energy prices on the basis of international crude oil prices per barrels and ignore the cost of government taxes, transportation cost, profits of the organization (Qasim et al, 2021;Iqbal et al, 2021;Aziz et al 2016;Saleem & Ahmad, 2015). The energy prices on the basis of international crude oil prices is not a good measure of domestic energy prices.…”
Section: Figure 2 Consumer Price Index(cpi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Besides this, the contribution of Islam also explored the influence of human development, money supply, and exchange rates on inflation and suggested that both money supply and exchange rates stimulate inflation in South Asian economies. The impact of petrol prices and exchange rates on inflation was captured by Qasim et al (2021) for Pakistan's economy. They confirmed that inflation was increasing due to an increase in petrol prices, but it was decreasing due to an increase in the exchange rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results of the DCC-GARCH model verified that there is a positive correlation between wholesale price index (proxy of Inflation) and crude price of oil and it is most near to one except crises period 2007-09 when it became negatively correlated due to lush fluctuations in the rate of exchange of Indian currency during crises period. Qasim et al, (2021) investigated links between the price of oils, ERR and the Islamic stock market of Malaysia with the help of the Vector Autoregressive (VAR) Model. After testing the collected data of Malaysia by using the Vector Autoregressive Model VAR model and Vector Error correct Method, it concluded that there are positive and significant relationships between the crude price of oil and Islamic stock return but the negative and meaningless link with foreign ERR.…”
Section: Literature Reviewmentioning
confidence: 99%